Isolation and sequence-specific DNA binding of the Antennapedia homeodomain. - Müller, M (1988)
The homeodomain encoded by the Antennapedia (Antp) gene of Drosophila was overproduced in a T7 expression vector in Escherichia coli. The corresponding polypeptide of 68 amino acids was purified to homogeneity. The homeodomain was analysed by ultracentrifugation and assayed for DNA binding. The secondary structure of the isolated homeodomain was determined by nuclear magnetic resonance spectroscopy. DNA-binding studies indicate that the isolated homeodomain binds to DNA in vitro. It selectively binds to the same sites as a longer Antp polypeptide and a full-length fushi tarazu (ftz) protein. Therefore, the homeodomain represents the DNA-binding domain of the homeotic proteins.